Health Education in Upper Secondary Schools – Assumptions and Opportunities of Implementation in the Light of the Curriculum - Pankowska, Dorota (Przegląd Badań Edukacyjnych (Educational Studies Review), 2020)
The effectiveness of health education, an important area of school education, depends on many factors. One of them is the conceptual layer expressed in the core curriculum. The aim of the research presented in this article was to check whether the learning objectives and content in Polish upper secondary school curricula are consistent with theoretical assumptions based on the achievements of health pedagogy. Qualitative and quantitative content analysis was used. First, the main assumptions of school health education were reconstructed to define analytical categories for further research (dimensions of health in a holistic model, concepts of health, pillars of health education, and methodological approaches). Then, the learning objectives and content of the 2018 core curriculum for Polish upper secondary schools were analysed. The obtained results indicate insufficient compliance of objectives and content with the assumptions of health education, which suggests the existence of a hidden program in this area already at the conceptual level.